Effects of Funding Fluctuations on Software Development: A System Dynamics Analysis. Issue 2 (2nd April 2016) - Trammell, Major Travis I.; Moulton, Allen; Madnick, Stuart E.
Abstract: What happens when software project funding is temporarily cut off and then restored at a later date? Although project funding gaps clearly result in software delivery delays, it is difficult to understand the causes and estimate the relative magnitude of the impact. This article uses System Dynamics modeling to examine how gaps in funding affect software development productivity and product delivery delay. Results provide software engineering managers with an improved sense of the negative effect of budget fluctuations. Two key insights for practicing engineering managers include a Ramp Up Tax that slows development and a Gap Tax due to the loss of project-related skill and familiarity when developers are transferred off a project and then return. Model experiments presented allow managers to compare the impact of temporarily stopping a project versus stretching out a project by temporarily reducing the funding level. Both the model and the patterns of results can provide project managers with a stronger basis for explaining the negative effects of funding gaps to senior leadership and funding managers.